PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN TANAMAN PANGAN PROVINSI JAMBI - Lili Andriani (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Purpose of this study was to : (1) Determine the level of organization culture, leadership and performance of employees at Dinas Pertanian Tanaman Pangan Provinsi Jambi, (2) Determine the effect of organization culture to the performance of employees at Dinas Pertanian Tanaman Pangan Provinsi Jambi, (3) Determine the influence of leadershipon the performance of employees at Dinas Pertanian Tanaman Pangan Provinsi Jambi, and (4) Determine effect simultaneously of organization culture, leadership and performance of employees at Dinas Pertanian Tanaman Pangan Provinsi Jambi. Organization culture is a system to believe and score amend in a organization to actuated employes behavior. (Soedjono, 2005:23). Leadership are “domination accessin potential individual to pushor invete the other people for do something strength of employes income, and has special capability in the rigt time and right place. (Kartono, 2003:1).Meanwhile, performance is what the employee do or not to do. (Mathis & Jackson,2001:78). This method study analysis is quantitative and descriptive. The population in this study is the Dinas Pertanian Tanaman Pangan Provisi Jambi. Research sampling stratified sampling technique. The total sample in this study were 71 respondents. Data on the analysis using a 2 (two) ways, namely (1) Using multiple linear regression to determine the factors that affect the quality of employee by the t test and F test at the significance level (α = 0.05), (2) Using the coefficients determination to determine the factors that affect the quality of employee with the simultaneous value of the coefficient of determination (R2) and partial (r2). The results showed, mean class for the respondent rejoinder of organizational culture variable (X1) is 291,22% and mean class for the respondent rejoinder of leadership variable (X2) is 325,90%, this result show the biggest score of mean class for the respondent rejoinder are leadership variable (X2). The amount of variables influence the performance of organizational culture to the Dinas Pertanian Tanaman Pangan Provinsi Jambi amounted to 3.998%. The influence of variables on the performance of leadership of Dinas Pertanian Tanaman Pangan Provinsi Jambi amounted to 2.523%. The effect of variable organizational culture, leadershipto the performance simultaneous of an employee of Dinas Pertanian Tanaman Pangan Provinsi Jambi amounted to 3.086% (X1) and 2.866% (X2).Keyword: organizational culture, leadership